2013
DOI: 10.1063/1.4816286
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of strain field in strained-channel-transistor arrays by scanning moiré fringe imaging

Abstract: We have applied scanning moiré fringe (SMF) imaging in scanning transmission electron microscopy (STEM) to the quantitative measurement of a strain field introduced in p-type channels of transistors with an embedded Si1−xGex source and drain. The compressive strain field parallel to the channels was revealed by the SMF image. We showed that the quantitative strain profile extracted from the SMF image was coincident with the independent measurement by a high-resolution STEM image. In addition, we demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…A quantitative method for strain field measurement by SMF imaging has been developed by the authors, 10,12 and we have shown that SMF imaging can be applied to the quantitative strain field measurement in the practical electronic device structures. 11 In this Letter, we report on quantitative measurement by SMF imaging of the strain field around the CoSi 2 embedded in the Si matrix of the S/D region of a transistor. The atomic rearrangement of the CoSi 2 /Si (111) interfacial structure formed at the S/D region was determined with high-resolution (HR)-STEM images.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A quantitative method for strain field measurement by SMF imaging has been developed by the authors, 10,12 and we have shown that SMF imaging can be applied to the quantitative strain field measurement in the practical electronic device structures. 11 In this Letter, we report on quantitative measurement by SMF imaging of the strain field around the CoSi 2 embedded in the Si matrix of the S/D region of a transistor. The atomic rearrangement of the CoSi 2 /Si (111) interfacial structure formed at the S/D region was determined with high-resolution (HR)-STEM images.…”
mentioning
confidence: 99%
“…8,9 Among the various techniques, a technique using scanning moir e fringe (SMF) by STEM imaging has been recently developed, and it can be used to measure strain fields at nanometer-scale spatial resolutions. [10][11][12][13] The SMFs 14 appear in high-angle annular dark-field STEM (HAADF-STEM) 15 images when the scanning grating size d s is close to integer multiples of the lattice spacing d l of the crystal structure (d s $ nd l : n ¼ 1, 2, 3, ….). Figure 1(a) 10 is an illustration of the SMFs formed by a superposition of a parallel scanning grating (green lines) and strained crystal lattices (black lines).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SMF imaging is a recently developed method that can measure strain fields at a high spatial resolution in the nanometer scale. [20][21][22] In the HAADF-STEM experiment, the SMFs appear when the scanning grating size d s is close to the crystal lattice spacing d l . Figure 1a shows the strained lattice spacing d l that increases from the bottom to the top of the pattern.…”
mentioning
confidence: 99%
“…We confirmed that the detector's inner angle of 45 mrad allowed us to obtain STEM image in HAADF regime. 21 The SMF images shown here were acquired at a magnification of 640 K with an acquisition time (dwell time) of 2 μs for each pixel. In order to obtain strain maps parallel to the strained channel, the translational SMFs formed by interfering scanning grating with the (220) lattice d-spacing of Si crystal were obtained and examined.…”
mentioning
confidence: 99%